Naturaleza muerta - Mott, Cynthia, author; Dormer, James T., advisor; Orman, Jack L., advisor; Voss, Gary Wayne, committee member; Turner, Ronny E., committee member (Colorado State University. Libraries, 1995)
I am constantly seeking out images that surround my daily life. I am attracted to the refuse of man-made objects that are left behind in varying states of decay. They become the records of existence, of the comings and goings, of ordinary people. I identify with these images, attracted by the repetition of patterns and shapes. The redundancy of daily habits are reiterated by fences, buildings, and chairs. Basic elements create patterns, asserting control within a space, reflecting the human need to organize and define. Structure and shape may overtake the recognition of objects transcending the normal realm. Life is rarely static. These inanimate objects mirror the same cycle of birth and death as our own lives. They force us to confront our own mortality. My work visually embodies our inevitable place in the life cycle through the cultural aesthetic of the built environment.
Zip file contains 14 slides of artist's works.
Keywords: Life in art; Lithography; Etching -- Technique